Closed Reduction and Cast Versus Percutaneous Pinning in Distal Radius Fracture - Shrestha, Bipan; Pandey, A; Singh, G P; Shrestha, K M; Shrestha, R (Journal of Universal College of Medical Sciences, 2018)
BACKGROUND:There is much debate regarding the optimal treatment of displaced distal radius fracture. The purpose of this prospective study was to compare functional and radiological outcomes of displaced distal radial fracture treated with cast or percutaneous pin.MATERIALS & METHODS: Sixty patients of all age groups with non comminuted extra-articular and partially articular fracture of the distal radius were included in this study. After randomization, thirty patients were treated with cast and thirty patients with percutaneous pins. For pin group below elbow volar slab was applied for three weeks. After three weeks, slab was removed and wrist physiotherapy started. Depending on radiological and clinical union, cast or pin was removed at around six to eight weeks. Follow-up was conducted at 1 week, 3 weeks, 6 weeks, 9 weeks, 3 months and 6 months. Radiographic assessment was done at each visit, while functional scores were obtained at 6 weeks, 9 weeks, 3 months and 6 months. Outcomes at fixed time points were compared between two groups with standard statistical methods.RESULTS: Mean age group in pin and cast group was 27 and 42 years respectively. Other than age, both the groups were identical with respect to sex, side and dominance of hand. Overall Pin group had better functional and radiological outcome than cast group. Pin group also had better Satio grading (p 0.002) where 96.6% of cases had excellent to good result unlike cast group where only 76.7% of cases achieved these result. Complication rate also were higher in cast group especially radial collapse (p